Creating authentic connectedness online through a shared experience of 'not-knowing'. Issue 1 (2nd January 2023) - Wolbert, Lynne; Ünlüsoy, Aslı
ABSTRACT: This article describes the experience of two educators in a master program in Pedagogy in the Netherlands. Their experience is of an online gathering with students and educators that took place during the COVID-19 pandemic. Students and educators were not allowed to meet face-to-face, thus resorted to online education. What happened at that online gathering was that the educators observed how the group connected to each other in a way that was reminiscent of the 'normal' face-to-face gatherings before the pandemic, but had been absent since the group was forced to meet online. The article starts with individual, subjective descriptions of this experience by the two educators. Subsequently, these so-called thick descriptions are interpreted and analysed. The purpose of zooming in on this particular experience is to gain insight into what pedagogical forms contributed to the enabling of this perceived authentic connectedness in the digital sphere.